2001
DOI: 10.1021/ma0102159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chain Ends and Chain Entanglement on the Glass Transition Temperature of Polymer Thin Films

Abstract: Monodispersed polystyrene with different molecular weights, M w, from below the entanglement molecular weight, M e (∼20K Da), to well above was studied for effects of chain ends and chain entanglement on the glass transition temperature, T g, of polymer thin films. The relative importance between these two effects is expected to reverse as M w crosses over M e. We found that the T g generally decreases with decreasing film thickness, t, consistent with previous findings. The difference between results from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
176
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 15 publications
17
176
1
1
Order By: Relevance
“…1(a). The results obtained in this study for the 5:0 kg=mol PS system are consistent with those of Tsui and Zhang [23] who studied PS films of M w 13:7 and 550 kg=mol and mixtures thereof and found that the nanoconfinement effect is independent of molecular weight for supported PS films. [A very different system, poly(methyl methacrylate) on SiO x substrates treated with hexamethyl disilazane, has reportedly shown [24] suppression of T g -nanoconfinement effects for molecular weights of 5 and 12 kg=mol; further study of the different effects of molecular weight in this system is warranted.…”
supporting
confidence: 91%
“…1(a). The results obtained in this study for the 5:0 kg=mol PS system are consistent with those of Tsui and Zhang [23] who studied PS films of M w 13:7 and 550 kg=mol and mixtures thereof and found that the nanoconfinement effect is independent of molecular weight for supported PS films. [A very different system, poly(methyl methacrylate) on SiO x substrates treated with hexamethyl disilazane, has reportedly shown [24] suppression of T g -nanoconfinement effects for molecular weights of 5 and 12 kg=mol; further study of the different effects of molecular weight in this system is warranted.…”
supporting
confidence: 91%
“…박막의 두께가 감소함에 따라 무정형 고분자 물질 에서 중요한 유리전이온도(T g )가 변화하는 것으로 알려져 있 으며, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] 이와 관련된 연구가 freestanding 상태 혹은 기질 (substrate)에 코팅된 상태(supported film)에서 spectroscopic ellipsometry, 1-7 X-ray reflectivity, 8 Brillouin scattering, 9 differential scanning calorimetry 10,11 등을 사용하여 지속적으로 진행되고 있다. Freestanding polystyrene (PS, M w =767000) 박막의 경우 두께 변화에 따른 T g 를 측정한 결과 박막의 두께 가 약 70 nm 이하에서 T g 가 감소하기 시작하여 약 30 nm에 서는 70 o C의 T g 감소를 보였고, 2,6 freestanding PMMA 박막 의 경우도 100 nm 이하의 두께에서 T g 가 감소하기 시작하여 약 30 nm 두께에서 20 o C 정도 T g 가 감소한다는 보고가 있다.…”
Section: 서 론unclassified
“…Later, other supported polymer films were also found to demonstrate an increase in T g with decreasing film thickness, such as poly(2-vinyl pyridine) on acidcleaned silicon oxide. 20 A layered model is one of the earliest models proposed to explain these observations, [18][19][20][21][22][23][24][25] and by far the most accepted for the thickness dependence of the T g of polymer films. The model presupposes that the molecular motions near the polymer-air interface are much faster than those in the bulk polymer, which can be due to segregation of chain ends to the surface 24,26 or a reduction in the chain entanglement near the polymer free surface.…”
Section: Experimental Observations On the T G Of Polymer Filmsmentioning
confidence: 99%
“…20 A layered model is one of the earliest models proposed to explain these observations, [18][19][20][21][22][23][24][25] and by far the most accepted for the thickness dependence of the T g of polymer films. The model presupposes that the molecular motions near the polymer-air interface are much faster than those in the bulk polymer, which can be due to segregation of chain ends to the surface 24,26 or a reduction in the chain entanglement near the polymer free surface. 24,27 On the other hand, the molecular motions at the polymer-substrate interface can be faster or slower than the polymer motions in bulk depending on whether the polymer-substrate interactions are sufficiently weak or strong, respectively.…”
Section: Experimental Observations On the T G Of Polymer Filmsmentioning
confidence: 99%